The potential of coconut waste element as an alternative material for roof ceiling purpose - Shariat, Norehan; Sanusi, Shahmir Hayyan (FAZ Publishing, 2020)
Nowadays, number of people diagnosed with mesothelioma (disease that could cause death) due to exposure of asbestos increased year by year. To overcome this issue, a study was conducted to investigate the potential of natural fibers that could be used to replace the usage of asbestos in ceiling application. Mixture of coconut shells, coconut fibers and sodium silicate (Na2O3Si) under different composition were analysed to assess its potential to replace the used of asbestos ceiling. The analysis which consist of Bending Test (mechanical properties), Thermal Analysis (thermal absorption rate), and Porosity Test (sound absorbtion coeeficient) were conducted on the natural fibre samples and comparison was made with the asbestos ceiling samples. From the results, it was found that sample with the composition of 70% sodium silicate, 15% coconut fiber and 15% powder coconut shell is the best and most suitable materials to be used as natural fiber ceiling purpose.